Trends in family communication patterns and parent-adolescent relationship: implications for research in Nigeria (2019)
This paper critically examines studies that have researched into parent-adolescent relationships with particular interest in the communication patterns through which such relationships are enacted. It reviews existing literature on parent-adolescent relationship research globally against the backdrop of parent-adolescent relationship research in Nigeria. It seeks to find out the research methods, sampling techniques, and the methods of data analysis adopted in studies investigating parent adolescent relationships globally. Adopting the Systems theory and Rules theory as theoretical framework for the analysis; the study used content analysis to generate data from various scholarly articles published in recognised academic journals, E-books and doctoral theses accessed via online databases. The primary basis for the selection of any article for analysis is that such article must focus on issues and themes on family communication patterns and parent-adolescent communication in parent adolescent relationships with exceptional interest in Nigeria. Most of the reviewed studies about (85%) were conducted in European nations while about (15%) were conducted in African nations. Majority of the studies (71.3%) adopted survey while 28.7% utilised the mixed method design. Most of the reviewed studies adopted the convenience sampling and purposive sampling techniques but employed multi-methods in their data analysis. This study suggested that more research efforts should be invested in communication and parent adolescent relationship in Nigeria to fill the gap created in parent-adolescent relationship literature in Nigeria.